2013
DOI: 10.7150/ijms.5994
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Laparoscopic Salpingectomy for Surgical Treatment of Tubal Pregnancy: Comparison with Multi-Port Laparoscopic Salpingectomy

Abstract: BackgroundThis study investigates the safety and feasibility of transumbilical single-port laparoscopic salpingectomy (SPLS) using conventional laparoscopic instruments compared to conventional multi-port laparoscopic salpingectomy (MPLS) for surgical treatment of tubal pregnancy.Material and methods We conducted a retrospective analysis of 63 patients with tubal pregnancy who underwent SPLS and 71 patients who underwent conventional MPLS between January 2008 and December 2010. All patients in the SPLS group h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…2a) [14-16, 18]. When considering only patients with hemoperitoneum, the pooled analysis data from 3 studies showed no differences among the 2 procedures (mean difference –5.46 [95% CI –38.85 to 27.92], p = 0.75, random-effects model; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2a) [14-16, 18]. When considering only patients with hemoperitoneum, the pooled analysis data from 3 studies showed no differences among the 2 procedures (mean difference –5.46 [95% CI –38.85 to 27.92], p = 0.75, random-effects model; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled analysis data from the 4 studies reporting data on the number of patients requiring transfusions of units of PRBC showed no significant differences among the 2 groups (OR 0.97 [95% CI 0.58–1.61], p = 0.90, fixed-effects model; Fig. 3b) [14, 16-18]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations